Respuesta :

Answer:

The 13th term is 81x + 59.

Step-by-step explanation:

We are given the arithmetic sequence:

[tex]\displaystle -3x -1, \, 4x +4, \, 11x + 9 \dots[/tex]

And we want to find the 13th term.

Recall that for an arithmetic sequence, each subsequent term only differ by a common difference d. In other words:

[tex]\displaystyle \underbrace{-3x - 1}_{x_1} + d = \underbrace{4x + 4} _ {x_2}[/tex]

Find the common difference by subtracting the first term from the second:

[tex]d = (4x+4) - (-3x - 1)[/tex]

Distribute:

[tex]d = (4x + 4) + (3x + 1)[/tex]

Combine like terms. Hence:

[tex]d = 7x + 5[/tex]

The common difference is (7x + 5).

To find the 13th term, we can write a direct formula. The direct formula for an arithmetic sequence has the form:

[tex]\displaystyle x_n = a + d(n-1)[/tex]

Where a is the initial term and d is the common difference.

The initial term is (-3x - 1) and the common difference is (7x + 5). Hence:

[tex]\displaystyle x_n = (-3x - 1) + (7x+5)(n-1)[/tex]

To find the 13th term, let n = 13. Hence:

[tex]\displaystyle x_{13} = (-3x - 1) + (7x + 5)((13)-1)[/tex]

Simplify:

[tex]\displaystyle \begin{aligned}x_{13} &= (-3x-1) + (7x+5)(12) \\ &= (-3x - 1) +(84x + 60) \\ &= 81x + 59 \end{aligned}[/tex]

The 13th term is 81x + 59.